Enhancing Farmer Engagement in Climate Policy - Chevallier, Romy (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This PowerPoint Presentation was provided to the East Africa Farmers Federation Workshop May 30-31, 2023. The objectives of the presentation are two fold - to look backwards and consider the next steps on agriculture in the climate negotiations and to enhance farmer engagement in climate change. The presentation provides the background on agriculture in the climate negotiations (from 1992-2018) with detailed explanations of the Koronivia Joint Framework and its evolution from 2020-2023, and details of Sharm el-Sheikh Joint Work implementation of climate action on agriculture and food security and what must be in place for COP28. The presentation examines climate policy windows outside of the UNFCCC taking place in the lead up to UNFCCC COP28 and African policy windows and engagement opportunities. Farmer engagement opportunities in national climate policies are described including the Nationally Determined Contributions (NDCs), their status for African Countries and how to ensure NDCs reflect farmer interests. Long Term Strategies are described. The presentation details how to strengthen farmer participation in climate policy at multiple levels and through various channels as well as recommendations for strengthening farmers' agency for engagement in climate policy.